The role of the Met98Lys optineurin variant in inherited optic nerve diseases. Issue 11 (2nd August 2006) - Craig, J E; Hewitt, A W; Dimasi, D P; Howell, N; Toomes, C; Cohn, A C; Mackey, D A
Abstract : Aims: To investigate the role of the common OPTN Met98Lys variant as a risk allele in open-angle glaucoma (OAG), autosomal dominant optic atrophy (ADOA) and Leber's hereditary optic neuropathy (LHON). Methods: The presence of the Met98Lys variant was determined in a total of 498 (128 with normal-tension glaucoma (NTG)) patients with OAG, 29 patients who had myocilin-related OAG, 101 patients from ADOA pedigrees, 157 patients from LHON pedigrees and 218 examined OAG age-matched normal controls. Results: 17 of 218 (7.8%) controls had the Met98Lys variant. 28 (5.6%) patients with OAG were Met98Lys positive. More Met98Lys carriers were found in the NTG group than in the high-tension glaucoma (HTG) group (p = 0.033). However, no significant difference was observed between the NTG and control cohorts (p = 0.609). Two MYOC mutation carriers were found to have the variant. The variant was found in 1 of 10 pedigrees with ADOA and in 8 of 35 pedigrees with LHON. Conclusion: Data from this study do not support a strong role for the OPTN Met98Lys variant in glaucoma, ADOA or LHON. However, a weak association was observed of the variant with NTG compared with that with HTG. Meta-analysis of all published data on the variant and glaucoma confirmed that the association, although weak, is highly statistically significant in the cohort with glaucoma versus controls.